2011
DOI: 10.5194/bg-8-1053-2011
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of soil organic carbon stocks in France

Abstract: Abstract. Soil organic carbon plays a major role in the global carbon budget, and can act as a source or a sink of atmospheric carbon, thereby possibly influencing the course of climate change. Changes in soil organic carbon (SOC) stocks are now taken into account in international negotiations regarding climate change. Consequently, developing sampling schemes and models for estimating the spatial distribution of SOC stocks is a priority. The French soil monitoring network has been established on a 16 km × 16 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
99
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(114 citation statements)
references
References 53 publications
10
99
3
2
Order By: Relevance
“…This is largely attributed to the humid climate and high natural vegetation (i.e., forest and wetland) cover. In this study, we have observed that forestlands have a higher SOCD than grasslands, which is different from the SOC results for China reported by Wang et al (2004) and for France reported by Martin et al (2011). We attribute these differences to the climate zones on which these studies have focused.…”
Section: Soc Estimates In the Sanjiang Plaincontrasting
confidence: 56%
See 2 more Smart Citations
“…This is largely attributed to the humid climate and high natural vegetation (i.e., forest and wetland) cover. In this study, we have observed that forestlands have a higher SOCD than grasslands, which is different from the SOC results for China reported by Wang et al (2004) and for France reported by Martin et al (2011). We attribute these differences to the climate zones on which these studies have focused.…”
Section: Soc Estimates In the Sanjiang Plaincontrasting
confidence: 56%
“…In addition, the estimated SOCD value of 10.19 kg m −2 for the depth range of 0-30 cm in the study area is higher than the 7.70 kg m −2 observed in the Loess Plateau of China and the value of 5.91 kg m −2 for France (Martin et al, 2011). This is largely attributed to the humid climate and high natural vegetation (i.e., forest and wetland) cover.…”
Section: Soc Estimates In the Sanjiang Plainmentioning
confidence: 61%
See 1 more Smart Citation
“…However, the reliability of these estimates depends upon the quality and resolution of the land use and soil spatial databases. Moreover, due to the large spatial variability of SOC within the map units, an elevated density of soil sampling points is required to achieve accurate estimates (Liebens and VanMolle, 2003;Martin et al, 2011).…”
Section: Muñoz-rojas Et Al: Organic Carbon Stocks In Mediterraneamentioning
confidence: 99%
“…carbon models (Martin et al, 2011;Hashimoto et al, 2017;Hengl et al, 2017) including applications for SOC mapping (Grimm et al, 2008;Sreenivas et al, 2016;Yang et al, 2016;Hengl et al, 2017;Delgado-Baquerizo et al, 2017;Ließ et al, 2016;Viscarra Rossel et al, 2014).Machine learning methods do not necessarily allow to extract information about the main effects of prediction factors in the response variable (e.g., SOC); consequently, a selection strategy is always useful to increase the interpretability of machine learning algorithms. With this diversity of approaches one constant question is if there is a 5 method that systematically improve the prediction capacity of the others aiming to predict SOC across large geographic areas (e.g., Latin America).…”
mentioning
confidence: 99%